HFpEF and HFrEF exhibit different phenotypes as assessed by leptin and adiponectin. (1st February 2017) - Faxén, Ulrika Ljung; Hage, Camilla; Andreasson, Anna; Donal, Erwan; Daubert, Jean-Claude; Linde, Cecilia; Brismar, Kerstin; Lund, Lars H
Abstract: Background: Heart failure with reduced ejection fraction (HFrEF) exhibits a "reverse metabolic profile". Whether this profile exists in HF with preserved ejection fraction (HFpEF) is unknown. We tested the hypothesis that HFpEF and HFrEF are similar regarding concentrations of and prognostic impact of leptin and adiponectin. Methods: In patients with HFpEF( n = 79), HFrEF( n = 84), and controls( n = 71), we analyzed serum leptin and adiponectin concentrations, their correlations, and associations with outcome. Results: Leptin levels in HFpEF and HFrEF were increased ( p < 0.05) compared to controls; with the highest levels in HFpEF, median (IQR), 23.1 (10.2–51.0), vs. HFrEF 15.0 (6.2–33.2), and vs. controls 10.8 (5.4–18.9) ng/mL.There was no difference between HFpEF and HFrEF p = 0.125 (adjusted for gender, BMI and age). Leptin was inversely associated with NT-proBNP ( r = − 0.364 p = 0.001) and associated with better outcome in HFrEF (HR per ln increase of leptin 0.76, 95% CI 0.58–0.99, p = 0.044) but not in HFpEF. Crude levels of adiponectin were similar in HFpEF: 11.8 (7.9–20.1), HFrEF: 13.7 (7.0–21.1), and controls: 10.5 (7.4–15.1) μg/L. In men, adjusted similarly as leptin, there was no difference between HFpEF and HFrEF, p = 0.310 but, compared to controls, higher levels in HFpEF ( p = 0.044) and HFrEF ( p = 0.001). Adiponectin correlated positively with NT-proBNP; r = 0.396 p < 0.001 and higher levels were associated with adverse outcome only in HFrEF (HR per ln increase 2.88 (95% CI 1.02–8.14, p = 0.045). Conclusion: HFpEF and HFrEF share elevated levels of leptin and adiponectin. However, the concept of reverse metabolic profile could not be confirmed in HFpEF, suggesting that HFpEF might have a conventional metabolic profile, rather than a distinct HF syndrome.